Preparation and Characterization of Chitosan/Bentonite Composites for Cr (VI) Removal from Aqueous Solutions - Junjie Jia; Yanjun Liu; Shujuan Sun (Adsorption Science & Technology)
Chitosan/bentonite composites (CSBT) prepared by physical gelation were tested for the adsorption of Cr (VI) from aqueous solutions in this work. The composites were prepared at a mass ratio from 2 : 1 to 1 : 2, and a composite of 1 : 1 was found to be most suitable for efficient Cr (VI) removal. The influencing parameters, including temperature, adsorbent dose, and pH, were statistically optimized using response surface methodology (RSM) for the removal of Cr (VI). The pH was found to be the limiting factor during the adsorption process, and under the optimal conditions, namely, adsorbent dose of 400 mg/L, pH=3, and temperature of 298 K, 87.61% Cr (VI) would be removed expectantly. The mechanism of Cr (VI) removal by CSBT was discussed, and the protonation of amino groups on chitosan followed by the combination of -NH3+ and anionic hexavalent chromium was the primary driving force. In addition, the removal of Cr (VI) onto CSBT was monolayer adsorption with a maximum adsorption capacity of 133.85 mg/g by the Langmuir isotherm. CSBT follows a pseudosecond-order kinetic model, and within 1.5 h, adsorption was observed to reach equilibrium. The calculated thermodynamic functions clarified that the adsorption process was exothermic and spontaneous below 312.60 K. CSBT could be regenerated after desorption by 0.5 mol/L NaOH solutions and exhibited superior reusability after six cycles. This study demonstrated composites of chitosan/bentonite as eco-friendly bioadsorbents for the removal of Cr (VI) from aqueous environments.